2021
DOI: 10.1111/bcp.14887
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of free flucloxacillin in patients treated with oral flucloxacillin plus probenecid

Abstract: Oral flucloxacillin may be coadministered with probenecid to reduce flucloxacillin clearance and increase attainment of pharmacokinetic-pharmacodynamic (PK/PD) targets. The aims of this study were to develop a population PK model of free flucloxacillin when administered orally with probenecid, and to identify optimal dosing regimens for this combination.Methods: We performed a prospective observational study of adults (45 participants) treated with oral flucloxacillin 1000 mg and probenecid 500 mg 8-hourly for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…This is consistent with the PK/PD data that were the premise for the change to the outpatient cellulitis treatment pathway and suggested that high-dose flucloxacillin with probenecid achieved adequate time above the MIC for bacterial killing. 12 Our findings are supported in mild cellulitis by a 2021 study of cellulitis management in Auckland, New Zealand. 11 The Auckland study was a retrospective audit reviewing cellulitis outcomes before and after the implementation of a new cellulitis treatment pathway.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This is consistent with the PK/PD data that were the premise for the change to the outpatient cellulitis treatment pathway and suggested that high-dose flucloxacillin with probenecid achieved adequate time above the MIC for bacterial killing. 12 Our findings are supported in mild cellulitis by a 2021 study of cellulitis management in Auckland, New Zealand. 11 The Auckland study was a retrospective audit reviewing cellulitis outcomes before and after the implementation of a new cellulitis treatment pathway.…”
Section: Discussionsupporting
confidence: 68%
“…16 This is an approach supported by comparative oral bioavailability studies on coadministration of flucloxacillin and probenecid with food. 12,17 Limitations Since this study was a retrospective audit, we were unable to assess the accuracy of the clinical diagnoses of cellulitis. Several alternative conditions, including venous insufficiency, may have been misdiagnosed as cellulitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These preclinical data are further supported by observational studies reporting favourable outcomes for the management of staphylococcal infections using flucloxacillin with probenecid. 37 Furthermore, Grayson and colleagues 38 demonstrated favourable clinical outcomes with IV cefazolin plus probenecid compared with ceftriaxone for the treatment of moderate-to-severe cellulitis as part of a third-generation cephalosporin-sparing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Improved MIC target attainment and reduced dosing intervals of antibiotics such as flucloxacillin can be achieved by combination with oral probenecid. Research has shown that T > MIC can be attained using flucloxacillin 1000 mg and probenecid 500 mg three times a day (no special timing in association with food is required) [4,5]. The use of probenecid enhanced oral antibiotic regimens in place of IV antibiotic treatment is now utilised in a number of places.…”
mentioning
confidence: 99%